2013
DOI: 10.1158/0008-5472.can-12-3461
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized 13C-Pyruvate Magnetic Resonance Reveals Rapid Lactate Export in Metastatic Renal Cell Carcinomas

Abstract: Renal cell carcinomas (RCCs) are a heterogeneous group of tumors with a wide range of aggressiveness. Noninvasive methods to confidently predict the tumor biological behavior and select appropriate treatment are lacking. Here, we investigate the dynamic metabolic flux in living RCC cells using hyperpolarized 13C-pyruvate magnetic resonance spectroscopy (MRS) combined with a bioreactor platform, and interrogated the biochemical basis of the MRS data with respect to cancer aggressiveness. RCC cells have signific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 51 publications
7
105
0
Order By: Relevance
“…In addition, in mouse xenograft models of human colorectal and breast cancer, release of lactate from tumor cells through MCT4 (and not the isoform MCT1) is sufficient to increase tumor growth (22). Moreover, lactate efflux mediated by MCT4, which can be explored in RCC cells by hyperpolarized 13 C-pyruvate magnetic resonance, was significantly higher in a metastatic RCC cell line with increased MCT4 expression (12). In line with these data, MCT4 expression in ccRCC of our cohorts as well as DNA methylation at specific CpG units was strongly associated with various clinicopathologic features, including sarcomatoid differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in mouse xenograft models of human colorectal and breast cancer, release of lactate from tumor cells through MCT4 (and not the isoform MCT1) is sufficient to increase tumor growth (22). Moreover, lactate efflux mediated by MCT4, which can be explored in RCC cells by hyperpolarized 13 C-pyruvate magnetic resonance, was significantly higher in a metastatic RCC cell line with increased MCT4 expression (12). In line with these data, MCT4 expression in ccRCC of our cohorts as well as DNA methylation at specific CpG units was strongly associated with various clinicopathologic features, including sarcomatoid differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide siRNA screening studies in a ccRCC cell line (11) showed that MCT4 may represent a promising metabolic key protein in ccRCC. Moreover, MCT4-mediated lactate efflux, explored in RCC cells by hyperpolarized 13 C-pyruvate magnetic resonance, was significantly higher in metastatic RCC cells (12). However, detailed analyses not only of its expression, but more importantly of the regulation of MCT4 in ccRCC are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Cells and authenticated using STR profiling, October 2012). The UOK262 cells were also encapsulated in alginate microspheres identical to prior publications 40 from our group. To model the inflammatory response, a mouse macrophage cell line, J774A.1, was obtained from ATCC.…”
Section: Methodsmentioning
confidence: 99%
“…Renal cell carcinomas (RCCs) are a broad group of tumors affecting the kidney that have been studied in some detail using hyperpolarized 13 C. In vitro HP [1- 13 C]pyruvate studies of two different RCC cell lines (UOK262 and UMRC6) and healthy proximal tubule epithelial (HK-2) cells have shown that the observed pyruvate to lactate ratio and the ratio of HP intracellular lactate to extracellular lactate (efflux ratio) can be used to distinguish the three different cell lines from each other [262,263]. Furthermore, the HP lactate efflux ratio strongly correlates with MCT4 mRNA expression, suggesting its potential use as a biomarker for differential diagnosis of RCCs.…”
Section: Hyperpolarized Studies By Organ Systemmentioning
confidence: 99%